2017
DOI: 10.1111/are.13537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on growth performance of greater amberjack (SERIOLA DUMERILIRisso 1810) Juveniles

Abstract: In order to successfully diversify Mediterranean aquaculture, it is necessary to determine optimum culture conditions of potential candidate species such as greater amberjack (Seriola dumerili). Among culture conditions, rearing temperature is a key factor for achieving optimum growth and maintaining fish welfare. However, little is known about the optimum culture conditions of greater amberjack (Seriola dumerili).Thus, the aim of this study was to determine the effect of three different rearing temperatures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 69 publications
7
18
0
1
Order By: Relevance
“…In another study on wild-caught greater amberjack reared under natural seawater temperatures, feed intake was also found to decrease at temperatures lower than 12°C (Skaramuca et al 2001). In accordance to the previous studies, better performance, in terms of growth and feeding parameters, was found in tank-reared greater amberjack at 26°C, with respect to 17 and 22°C in a study conducted in Spain (Fernández-Montero et al 2017). In the HCMR cage facilities, feeding is reduced at temperatures < 16°C, and the sh return to feeding normally at temperatures > 19°C (personal observations).…”
Section: Discussionsupporting
confidence: 82%
“…In another study on wild-caught greater amberjack reared under natural seawater temperatures, feed intake was also found to decrease at temperatures lower than 12°C (Skaramuca et al 2001). In accordance to the previous studies, better performance, in terms of growth and feeding parameters, was found in tank-reared greater amberjack at 26°C, with respect to 17 and 22°C in a study conducted in Spain (Fernández-Montero et al 2017). In the HCMR cage facilities, feeding is reduced at temperatures < 16°C, and the sh return to feeding normally at temperatures > 19°C (personal observations).…”
Section: Discussionsupporting
confidence: 82%
“…Data are from (Fernández-Montero et al, 2017;Fonds et al, 1992;Handeland et al, 2008;Hofmann and Fischer, 2003;Kinne, 1960;Koskela et al, 1997;Mesa et al, 2013;Ojanguren et al, 2001;Remen et al, 2016;Schram et al, 2013;Sun and Chen, 2009;Sun and Chen, 2014;Xie et al, 2010;Zanuzzo et al, 2019).…”
Section: Aerobic Scope Protection By Reduction Of Food Intakeunclassified
“…While the evacuation of the stomach may last less than one day, the evacuation of the intestine may last 36 to 48 h. These values are only indicative for median sized farmed fish with daily feeding. Different factors such as feeding frequency, ration size, feed quality, body size and water temperature have been described to affect transit time in fish (Miegel et al, 2010), particularly the last one (De et al, 2016;Fernández-Montero et al, 2018;Handeland et al, 2008;Temming and Herrmann, 2001). According to these studies, transit time increases with the temperature except at extremely high values.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the feed intake increases with increased temperatures up to levels close to the upper tolerance limits (Fernández-Montero et al, 2018;Pérez-Casanova et al, 2009). Digestive enzyme activity has been traditionally assessed in two ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation